Features of the creation the promotional video industrial company by means of computer graphics - Savchenko, L.; Vorontsova, D.; Krukovsky, В. (Theory and practice of design, 2015)
Based on the developed scenario promo video manufacturing company in the production and installation of steel structures are considered particularly the creation of three-dimensional objects for five scenes, their subsequent animation and visual effects modeling software environment MAXON CINEMA 4D.